The concept of security - Kostić Mladen S. (Војно дело, 2016)
Since the end of World War II, national security has been much discussed in academic and political circles in terms of foreign and international policies. No social term or concept was so much misused and misinterpreted as national security. Therefore, this paper is an effort to explain the concept of security in broader context, in order for it to be applicable at a number of levels, but with a special focus on national security. Security is defined as a political goal, clear enough to be distinguished from other goals. To reach a closer conceptual definition, it is necessary to identify certain “specifications” or “qualifications” of security, which can facilitate the analysis of the expediency of security policy. If this term is to continue to be used in political analyses or theories, conceptual qualifications (specifications), which are explained here, will be necessary. As a start, the security can be set as a goal of politics, and then politics further determined as a means for achieving this goal.